(untitled) (Jurnal Pilar Nusa Mandiri, 2020)
library is a means of support for students to develop their potential by increasing their knowledge through books. good library management is needed to facilitate students to support their learning. SMK PGRI 2 Salatiga has a library. the system applied to manage this library uses conventional methods where all library data is recorded into books. This system has a weakness that is prone to errors in recording and searching data. To deal with this problem, we need a system that can help manage library data. library information system can assist library management because all data can be recorded into the system and accessed through the system. This research was conducted to build a library information system that implements the laravel framework as an application framework. Laravel has various functions that can be used to help web application development. Based on the application testing carried out, the library information system of SMK PGRI 2 Salatiga has been running according to design and can handle library data recording by implementing the functions of the laravel